Interpretation of The Phrase “Coercion” in The Compilation of Islamic Law as Reasons for Cancellation of Marriage - Neng Widya Millyuner; Adi Nur Rohman; Elfirda Ade Putri (KRTHA BHAYANGKARA, 2021)
Marriage is a common thing in society with ubudiyyah elements in it. However, legal issues often accompany the sanctity of the marriage bond itself, such as the cancellation of a marriage due to an element of coercion from a third party. Article 71 Compilation of Islamic Law (KHI) states that one of the reasons for being able to apply for a marriage cancellation is because of coercion when the marriage took place. The purpose of this study is to analyze the meaning of the phrase "coercion" as a reason for annulment of marriage and its accompanying legal implications. This type of research is classified as normative-empirical legal research using a statutory approach and a conceptual approach plus a sociological approach as a tool. This research refers to a variety of primary, secondary and tertiary legal materials compiled and traced through literature studies and interviews with judges of the Religious Courts. The legal materials that have been collected are then analyzed descriptively and analytically. The results showed that what is meant by coercion in marriage is a marriage that occurs not because of one's own will or feels that he is under threat. As a form of legal consequence, annulment of a marriage by force is different from divorce, where the marriage bond that occurred before the breakup of the marriage is considered never to have occurred.